PROFIL ASAM LEMAK DAN ASAM AMINO SUSU KAMBING SEGAR DAN TERFERMENTASI [Fatty Acid and Amino Acid Profile of Fresh and Fermented Goat Milk] - Maria Erna Kustyawati; . Susilawati; Dewi Tobing; . Trimaryanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
This research aimed to investigate the composition of fatty acids and amino acids in fresh and fermented goa-milk. The milk was in oculated with 4% (v/v) of L. casei and fermented at 37°C for 48 h. Analysis of fatty acids of fresh and fermented goat and cow’s milk was done by HPLC method, where as amino acid composition was analyzed by GC method. Twenty five semi-trained panelists evaluated the sensory characteristics of fermented milk. Results showed that the fermentation process changed fatty acid profile in goat milk. The saturated fatty acids found in fermented goat-milk were lauric, misristic, and palmitic acid while the unsaturated fatty acids were oleic, linoleic, and linolenic acid. The total amount of saturated fatty acid of fermented goat-milk was higher while unsaturated fatty acid was lower than those in fresh goat milk. The aroma of goaty flavor, strong and musky or “prengus”, was slightly detected in fermented goat milk. Linoleic acid was not detected in fermented goat milk and therefore it was less susceptible from oxidativedeterioration. On the other hand, the fermentation process did not change the profile of amino acids in goat milk. Fermented dairy product made from whole goat milkand cow’s milk was accepted by the panelist as it hadslightly sour taste, yellowish color, and slightly goaty flavor, yet it had high amount of saturated fatty acids.